Attachment-based psychotherapy helping patients develop adaptive capacities - Costello, Peter C. (American Psychological Association, 2013)
"This book explores in detail how our early attachment experiences with a primary caregiver affect our development into adulthood. In particular, it explores how suboptimal attachment experiences can lead to psychopathology (especially depression, anxiety, and maladaptive anger) and difficulties in interpersonal relationships. Finally, it describes how psychotherapy can mitigate the detrimental effects of negative early attachment experiences"--Chapter. (PsycINFO Database Record (c) 2013 APA, all rights reserved)